MATHEMATICS THROUGH LANGUAGE AND LANGUAGE THROUGH MATHEMATICS: CONDENSATION TRANSCRIPTION AS A POINT OF SYMBIOSIS - Hill, Janice (Physical and Mathematical Education, 2024)
This paper explores the idea of condensation transcription—which is defined as the reduction of lengthy collections of lexical elements or mathematical descriptions into short forms—as the point where mathematics and language learning cross-influence one another notably. To elaborate, condensation transcription is defined as the linguistic ability and procedure that permits the reconstruction and compacting of larger lexical sets into more manageable forms while maintaining the basic meanings of those sets. Such a phenomenon occurs when mathematical concepts are rewritten from page-long descriptions to figures and numerical entities, and when literary passages are compressed into their main ideas.Formulation of the problem. Word problems, main idea identifications, and essay writing are some of the most dreaded topics of study in mathematics and language. In order to suggest improvements in these challenging areas within the education of both disciplines, this paper’s research emphasizes the significance of condensation transcription and makes readers aware of it by examining lexical elements in language and mathematical entities, pinning their origins, and explaining what learning strategies can be extracted from language that could be useful in mathematics learning, and vice versa.Materials and methods. The resources used in this investigation include a comprehensive dictionary entry, a word problem, literary text passages, and written explorations of mathematical concepts, all of which are dissected through the implementation of condensation transcription’s conventional procedures, which are termed ‘analysis,’ ‘coding,’ and ‘decoding.’ This procedure is necessary to show, first-hand, how condensation transcription works and how it is applied, as well as what can be gleaned from its functions and applications.Results. The results point to condensation transcription being a basic concept in mathematics and language that powers mathematical learning through comprehension of language, and reversely.Conclusions. As a whole, this paper underscores the importance of having the knowledge of condensation transcription in language and mathematics. By recognizing the role of condensation transcription as a foundational language process, practitioners in both language and mathematics could make some of the most difficult concepts in both disciplines easier for students to grasp.
Keywords: Condensation Transcription; Analysis; Coding; Decoding; Mini Essay